The Mechanism of Diarrhetic Shellfish Poisoning Toxin Production in Prorocentrum spp.: Physiological and Molecular Perspectives - Thomas Chun-Hung Lee; Fiona Long-Yan Fong; Kin-Chung Ho; Fred Wang-Fat Lee (Toxins, 2016)
Diarrhetic shellfish poisoning (DSP) is a gastrointestinal disorder caused by the consumption of seafood contaminated with okadaic acid (OA) and dinophysistoxins (DTXs). OA and DTXs are potent inhibitors of protein phosphatases 2A, 1B, and 2B, which may promote cancer in the human digestive system. Their expression in dinoflagellates is strongly affected by nutritional and environmental factors. Studies have indicated that the level of these biotoxins is inversely associated with the growth of dinoflagellates at low concentrations of nitrogen or phosphorus, or at extreme temperature. However, the presence of leucine or glycerophosphate enhances both growth and cellular toxin level. Moreover, the presence of ammonia and incubation in continuous darkness do not favor the toxin production. Currently, studies on the mechanism of this biotoxin production are scant. Full genome sequencing of dinoflagellates is challenging because of the massive genomic size; however, current advanced molecular and omics technologies may provide valuable insight into the biotoxin production mechanism and novel research perspectives on microalgae. This review presents a comprehensive analysis on the effects of various nutritional and physical factors on the OA and DTX production in the DSP toxin-producing Prorocentrum spp. Moreover, the applications of the current molecular technologies in the study on the mechanism of DSP toxin production are discussed.